The development of Dancesport Entrepreneurship Curriculum for specific sports entrepreneurship learning outcome among Chinese sports students - Liu, Bin (Tanjong Malim, 2023)
The development of Dancesport Entrepreneurship Curriculum for specific sports entrepreneurship learning outcome among Chinese sports students by Liu, Bin